Sick of Leading? Supervisory Responsibility and Its Consequences for Sickness Absenteeism and Sickness Presenteeism - Stephanie Funk (Journal of Business and Psychology, 2024)
This research examines the impact of leadership positions with supervisory responsibility on two labor-market related health behaviors—sickness absenteeism and sickness presenteeism, i.e., working while being sick. Drawing on the job demands-resources (JD-R) model, this study posits that supervisory responsibility, serving as both a job resource and a demand, reduces sickness absenteeism while concurrently increasing sickness presenteeism behavior. The study identifies permanent availability and time pressure as two key aspects of leadership positions with supervisory responsibility that mediate these relationships. Using German-linked employer-employee data, the empirical results suggested that having supervisory responsibility reduces sickness absenteeism while at the same time elevating the engagement in sickness presenteeism. Furthermore, these relationships are partially mediated by leaders' need for permanent availability and the time pressure inherent in positions with supervisory responsibility. This research advances our understanding of job characteristics of leadership positions by illustrating that job demands can yield favorable outcomes, offering valuable insights into the complex interplay between leadership positions and leaders' health behaviors.
Keywords: 650; Supervisory responsibility; Leadership; Sickness absenteeism; Sickness presenteeism; Job demands-resources model